Understanding Knee Osteoarthritis: A Comprehensive Review - Girish, Leena; K T, Subhadra (Indian Journal of Integrative Medicine, 2025)
Background: Osteoarthritis (OA) is the most prevalent type of joint disorder, with the hip, knee, and metacarpophalangeal joints, as well as the cervical and lumbar vertebrae, being particularly susceptible. Knee osteoarthritis (KOA), the most common chronic degenerative joint disease, leads to significant morbidity and disability. The increasing life expectancy and an ageing population mean that KOA not only diminishes patients’ quality of life but also poses a public health challenge. Currently, there is no permanent cure for KOA. Available treatments primarily focus on alleviating symptoms and slowing disease progression. Effective management requires a strategy to address both clinical symptoms and disease progression. Initial treatment should be conservative and may include both pharmacological and non-pharmacological methods. Surgery may be considered as a last resort if conservative treatments are ineffective. This review synthesizes current knowledge on knee OA and its various treatment strategies for reducing pain and stiffness while improving patient functionality. Objectives: This study focuses on a comprehensive review of knee osteoarthritis and its currently available treatment modalities recommended for patients presenting with symptoms. Methods: A thorough literature search was carried out in search engines like PubMed and Google Scholars using following primary terms; "Osteoarthritis"; "Knee Osteoarthritis"; "Management of KOA"; "CAM therapy". Articles meeting the inclusion criteria were included in this review.